2022
DOI: 10.1155/2022/7786036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Intestinal Parasites and Enteric Bacterial Infections among Selected Region Food Handlers of Ethiopia during 2014–2022: A Systematic Review and Meta-Analysis

Abstract: Food-borne disease due to intestinal parasites (IPs) and enteric bacterial infections (EBIs) remain a major public health problem. Food handlers, individuals involved in preparing and serving food, working with poor personal hygiene could pose a potential threat of spreading IPs and EBIs to the public. The aim of this study was to examine the overall prevalence and risk factors of IPs and EBIs among food handlers in four selected regions of Ethiopia. Scientific articles written in English were recovered from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 93 publications
2
7
0
1
Order By: Relevance
“…The overall prevalence of IPIs among food handlers in this study was found to be 33.5%. This finding aligns with systematic review and meta-analysis studies from Ethiopia conducted at different times, which reported prevalence rates of 29.2 and 33.6% ( 13 , 41 ). Other studies from southern Ethiopia ( 14 , 29 , 42 ), Jimma town ( 43 ), Sudan ( 44 ), and Kenya ( 45 ) reported similar prevalence rates ranging from 29.4 to 39.2%.…”
Section: Discussionsupporting
confidence: 89%
“…The overall prevalence of IPIs among food handlers in this study was found to be 33.5%. This finding aligns with systematic review and meta-analysis studies from Ethiopia conducted at different times, which reported prevalence rates of 29.2 and 33.6% ( 13 , 41 ). Other studies from southern Ethiopia ( 14 , 29 , 42 ), Jimma town ( 43 ), Sudan ( 44 ), and Kenya ( 45 ) reported similar prevalence rates ranging from 29.4 to 39.2%.…”
Section: Discussionsupporting
confidence: 89%
“…Ethiopia's population was 113,881,451 in 2020, which is equivalent to 1.47%, according to Worldometer's analysis of the latest available United Nations data. In addition, the aforementioned analysis predicts that by 2020, 24,463,423 people, or 21.3% of the total population, will reside in urban areas 26,27 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the aforementioned analysis predicts that by 2020, 24,463,423 people, or 21.3% of the total population, will reside in urban areas. 26,27…”
Section: Country Profilementioning
confidence: 99%
“…In Ethiopia, the burden of intestinal parasites (IPs) is extremely high. A third (26 million), a quarter (21 million), and one in every eight (11 million) Ethiopians are infected with Ascaris lumbricoides, Trichuris trichiura, and hookworm, respectively (14)(15)(16). As a result, Ethiopia has the second, third, and fourth largest burdens of ascariasis, hookworm, and trichuriasis, in sub-Saharan Africa, respectively (17).…”
Section: Introductionmentioning
confidence: 99%